Pengaruh Work Life Balance terhadap Keterikatan Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada Biro Manajemen Barang Milik Negara (BMN) dan Pengadaan Sekretariat Jenderal Kementerian Keuangan - Martdinata, Sapta (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Work-life balance is crucial for employees as they navigate their dual roles as individuals and as employees. This study analyzes the impact of work-life balance on employee engagement, with job satisfaction serving as an intervening variable, at the Bureau of State Asset Management and Procurement of the Secretariat General of the Ministry of Finance. Work-life balance is considered an essential factor for employees in accomplishing their tasks to achieve organizational goals, which can influence job satisfaction and employee commitment to the organization. The research employs a quantitative method with a survey approach through the distribution of questionnaires. This study utilizes descriptive methods, multiple linear regression analysis, and the Sobel test. The findings indicate that work-life balance has a positive and significant effect on job satisfaction. Furthermore, job satisfaction also has a positive and significant impact on employee engagement. It can be concluded that job satisfaction, as an intervening variable, strengthens the relationship between work-life balance and employee engagement.